Dark Energy Survey Year 1 Results: A Precise H0 Estimate from DES Y1, BAO, and D/H Data. Issue 3 (20th July 2018) - Abbott, T M C; Abdalla, F B; Annis, J; Bechtol, K; Blazek, J; Benson, B A; Bernstein, R A; Bernstein, G M; Bertin, E; Brooks, D; Burke, D L; Carnero Rosell, A; et al.
ABSTRACT: We combine Dark Energy Survey Year 1 clustering and weak lensing data with baryon acoustic oscillations and Big Bang nucleosynthesis experiments to constrain the Hubble constant. Assuming a flat ΛCDM model with minimal neutrino mass (∑ m ν = 0.06 eV), we find H_0=67.4^+1.1_-1.2 km s^-1 Mpc^-1 (68 per cent CL). This result is completely independent of Hubble constant measurements based on the distance ladder, cosmic microwave background anisotropies (both temperature and polarization), and strong lensing constraints. There are now five data sets that: (a) have no shared observational systematics; and (b) each constrains the Hubble constant with fractional uncertainty at the few-per cent level. We compare these five independent estimates, and find that, as a set, the differences between them are significant at the 2.5σ level (χ 2 / dof = 24/11, probability to exceed = 1.1 per cent). Having set the threshold for consistency at 3σ, we combine all five data sets to arrive at H_0=69.3^+0.4_-0.6 km s^-1 Mpc^-1 .